China's move to measuring relative poverty: Implications for social protection - Robert Walker; Lichao Yang (International Labour Organization (ILO), 2021)
With rural extreme poverty officially eradicated in 2020, China is to move to measuring relative poverty in urban and rural areas. Relative poverty describes circumstances in which people cannot afford actively to participate in society and benefit from the activities and experiences that most people take for granted. It is conventionally defined as 40, 50 or 60 percent of national median disposable income. While a single poverty threshold symbolises national unity, separate poverty thresholds could be created for urban and rural areas or provinces. A unified national poverty standard for China based on 40 per cent of national median disposable income threshold implies income levels almost 4 times higher than the existing rural poverty line and 61 per cent higher than average social assistance (Dibao) payments in urban areas (often used as a surrogate urban poverty line). Relative poverty is more persistent than absolute poverty and less affected by economic growth. Research is required to determine the needs of peri-poor persons (i.e., those brought into poverty due to the new definition). Strategies needed to tackle relative poverty include: a comprehensive social protection system inclusive of floors; active policies to assist people out of poverty; poverty mainstreaming; and supportive, redistributive fiscal policies.
Keywords: 330; social protection; poverty; poverty alleviation